Human capital and innovation in the integration process of logging in the ejido Gómez Tepeteno, Tlatlauquitepec, Puebla - Sánchez-Vidaña, Diana Lorena; Valtierra-Pacheco, Esteban; González-Guillén, Manuel de Jesús; León-Merino, Aurelio (Instituto de Ecología, A.C., 2018)
The ejido Gomez Tepeteno took control of the use and management of their wood and non-wood forest resources in the 1970s. One of the most important processes they paid attention to was the development of staff capacity-building involved in logging and industrialization and, more recently, into the adoption of technological innovation processes. The objective of this study was to analyze the innovation process and human capital building in the integration of the timber forest chain in this ejido. The research was carried out using semi-structured interviews targeted to key actors, structured surveys to forest industry workers, and direct observation on all the productive phases. The results show that the ejido has made important achievements on human capital development on the following innovations: 1) the use of automatic data caliper to cubage and documentation of roundwood, 2) implementation of an accounting and financial control system, 3) production of kiln-dried wood from sawnwood of its own or processed for others, and 4) integration of a value network model for wood products. The ejido Gómez Tepeteno has understood that to improve wood production, they must generate permanent systems of technological innovations on logging and transformation processes that involve investment and capitalization in short, medium and long-terms.